Interactions of relativistic particles in stellar winds - Palacio, Santiago del (2014)
Several binary systems hosting a massive star and a companion that is either a similar star or a compact object, present non-thermal emission from radio to γ-rays. This non-thermal emission is the consequence of the interactions of relativistic particles surrounded by the stellarwind. Themain goal of thiswork is to characterize the high-energy physics of γ-ray binaries by implementing a general modeling for their most important high-energy processes. To thoroughly investigate the effects of the emitter-star-observer geometry on the resulting radiation, we sistematically applied a non-thermal leptonic model for different locations of the emitter, magnetic fields, and acceleration timescales. The results of this procedure are presented in the form of emissivity maps, which are useful for exploring statistical properties of γ-ray binaries as well as their expected distribution in the galaxy.